The Moderating Role of Financial Performance on Governance and Firm Characteristics toward Sustainability Disclosure - Saddam Hussin; Erna Setiany (LifeSciFi, 2025)
The growing importance of sustainability reporting has prompted companies to pay closer attention to factors influencing its disclosure. This study investigates the effect of board size, CEO educational background, firm size, and leverage on sustainability report disclosure, with financial performance acting as a moderating variable. The research focuses on energy sector companies listed on the Indonesia Stock Exchange that published both financial and sustainability reports between 2019 and 2023. Purposive sampling was employed to select the sample, and data were analysed using panel data regression in EViews 12, with hypothesis testing conducted through t-tests. The findings reveal that board size and CEO educational background do not significantly influence sustainability report disclosure, whereas firm size and leverage have a positive impact. Furthermore, financial performance moderates these relationships: it weakens the effect of board size and CEO education on disclosure, but strengthens the influence of firm size and leverage. These results highlight the critical role of financial performance in shaping sustainability reporting practices, providing insights for both policymakers and corporate management in promoting transparency and accountability.